Comparative Analyses of Diversity and Similarity Indices of West Bank Forest and Block A Forest of the International Institute of Tropical Agriculture (IITA) Ibadan, Oyo State, Nigeria - Ariyo Oluyinka Christopher (International Journal of Forestry Research)
Comparative analyses of diversity and similarity indices of west bank and block A forest of the International Institute of Tropical Agriculture (IITA) were carried out by the vegetation survey using transects and plot sampling techniques. Six transects {A (270°W), B (90°E), C (180°S), D, E (0°N), and F (180°W)} were constructed with the aid of prismatic compass in west bank forest and block A forest. 10 sampling plots of 10 m × 10 m were demarcated along each transect making 30 plots in each forest, and a total number of 60 plots were used for the study. Complete enumeration and identification of plants were carried out in each plot. The results showed that block A forest had 167 plant species from 58 families while west bank forest had 146 plant species from 56 families. A total number of 219 plant species from 70 families and 5804 individual plants were recorded in the two forests. West bank forest had higher values of all the diversity indices and Gamma diversity except Margalef’s community diversity index and alpha diversity index which were high in block A forest. Sorensen’s and Jaccard similarity indices of plants between west bank forest and block A forest were 59.42% and 42.66%, while the dissimilarity index of 40.58% was recorded. Thus, the two forests are richer and diverse in plant species; adequate protection of the two forests should be a priority to prevent loss of diversity of plants. Cutting of poles from the forests should be stopped.